(untitled) (Al Dzahab, 2025)
Purpose: This study aims to analyze the influence of Accounting Information Systems, Human Resources, and Leadership Style on the Effectiveness of Managerial Decision-Making in Micro, Small, and Medium Enterprises (MSMEs). Design/Methodology/Approach: This research employs a quantitative approach with a causal method. The sampling technique used is purposive sampling with a total of 100 respondents. Data were analyzed using multiple linear regression. Findings: The results indicate that Accounting Information Systems, Human Resources, and Leadership Style have a positive effect on the Effectiveness of Managerial Decision-Making. A well-functioning information system helps provide accurate and relevant data to support rational decision-making. High-quality human resources enhance analytical and interpretative abilities in the decision-making process. Meanwhile, visionary and participative leadership fosters a collaborative work environment that strengthens the effectiveness of managerial decisions. Research Implications: The success of decision-making in MSMEs depends not only on leadership capabilities but also on the support of reliable information systems and the competence of human resources. Therefore, improving managerial capacity in MSMEs should focus on strengthening information systems, developing human resource competencies, and applying adaptive leadership styles that respond to changes in the business environment.